2022
DOI: 10.3390/ijms23126839
|View full text |Cite
|
Sign up to set email alerts
|

Generation of TRIM28 Knockout K562 Cells by CRISPR/Cas9 Genome Editing and Characterization of TRIM28-Regulated Gene Expression in Cell Proliferation and Hemoglobin Beta Subunits

Abstract: TRIM28 is a scaffold protein that interacts with DNA-binding proteins and recruits corepressor complexes to cause gene silencing. TRIM28 contributes to physiological functions such as cell growth and differentiation. In the chronic myeloid leukemia cell line K562, we edited TRIM28 using CRISPR/Cas9 technology, and the complete and partial knockout (KO) cell clones were obtained and confirmed using quantitative droplet digital PCR (ddPCR) technology. The amplicon sequencing demonstrated no off-target effects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…We produced the FLAG-tagged acetylation-mimicking mutants of mouse Trim28, namely K255Q, K267Q, K290Q, and K305Q, as well as acetylation-defective mutants K255R, K267R, K290R, and K305R. These constructs were expressed in TRIM28 knockout human leukemia K562 cells [ 33 ] to test their interaction with Gal4 DNA-binding domain (Gal4 DBD )-KRAB. In an immunoprecipitation analysis, only K305Q had impaired interaction with recombinant Gal4 DBD -KRAB ( Figure 1 a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We produced the FLAG-tagged acetylation-mimicking mutants of mouse Trim28, namely K255Q, K267Q, K290Q, and K305Q, as well as acetylation-defective mutants K255R, K267R, K290R, and K305R. These constructs were expressed in TRIM28 knockout human leukemia K562 cells [ 33 ] to test their interaction with Gal4 DNA-binding domain (Gal4 DBD )-KRAB. In an immunoprecipitation analysis, only K305Q had impaired interaction with recombinant Gal4 DBD -KRAB ( Figure 1 a).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the megakaryocytic repressor IKAROS family transcription factors IKZF2 and IKZF3 and the paternally imprinted genes PEG3 and DLK1 were upregulated, and the embryonic and fetal globin repressor SOX6 , the maternally imprinted gene MEG3 , and melanoma antigen family members MAGEC1, MAGEC2, MAGEB1 , and MAGEA1 were downregulated ( Table S1 ). Previously, we had demonstrated that both SOX6 and MAGEC2 were downregulated in TRIM28 -KO cells, which were analyzed by cDNA microarray [ 33 ]. To further verify the up- or downregulation of these genes, we performed RT-qPCR ( Figure 3 d), which confirmed the changes in the expression of specific genes identified by RNA-seq of TRIM28 -K304Q cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tripartite motif-containing protein superfamily (TRIMs) are involved in diverse biological processes and play a crucial role in cancer therapy [ 26 , 27 , 28 , 29 , 30 ]. Recent evidence suggests that TRIM28 regulates the post-translational modification of proteins and participates in autophagy [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%